29th AIAA Applied Aerodynamics Conference 2011
DOI: 10.2514/6.2011-3791
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Bio-Inspired High Lift Effectors on a 2-D Airfoil

Abstract: JOHNSTON, JOE MONROE. Experimental Investigation of Bio-Inspired High Lift Effectors on a 2-D Airfoil. (Under the direction of Dr. Ashok Gopalarathnam). Flaps mounted on the upper surface of an airfoil, called Lift Enhancing Effectors, have been shown to increase maximum lift and stall angle in wind tunnel tests. These effectors are fabricated from 0.35 mm thick Mylar and are allowed to rotate freely about their leading edges. The tests were done in the NCSU Subsonic Wind Tunnel at a chord Reynolds number of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…In order to prevent flutter motion or fall-over of the flaps, their length, thickness, and material properties, such as bending stiffness, are crucial. Kernstine et al [4] and Johnston et al [6] reported additional drag on airfoils caused by flaps. This is in contrast to Liu et al [9], who reported significant reduction in drag.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to prevent flutter motion or fall-over of the flaps, their length, thickness, and material properties, such as bending stiffness, are crucial. Kernstine et al [4] and Johnston et al [6] reported additional drag on airfoils caused by flaps. This is in contrast to Liu et al [9], who reported significant reduction in drag.…”
Section: Introductionmentioning
confidence: 99%
“…This interaction between feathers and flow allows for better control of lift at high angles of attack. This positive effect on the lift coefficient could be adopted for technical applications by replacing feathers with flexible flaps [2][3][4][5][6][7]. Examples for usage include small wind turbines, where strong gusts could lead to sudden drops in lift and therefore induce strong mechanical loads.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 shows a duck and a raven, both with pop-up flap deployed during landing. This behaviour of bird wings has been mimicked in various experiments with a flap attached to the top surface of a wing (8)(9)(10)(11)(12)(13) . The flap is hinged about its leading edge and the trailing edge of the flap is left free.…”
Section: Background Information -High-lift Effectorsmentioning
confidence: 99%
“…16 showed a larger displacement in the z-direction between the upper and lower stream ribbon in flow initiated at z = 2.0 than the one initated at z = 1.0 (circled in blue); the observation shows that the flow feature that cause the displacement in stream traces is most likely initiated at the wingtip, but have little effect on flow closer to the root of the wing.By combining the observations fromFigure 7.14, 7.15 and 7.16, we can reach the conclusion that the primary three dimensional flow effect influencing the performance of the passive flap is the wingtip vortex. As the lift enhancement from the passive flap is due to its position at the optimal flap angle, the non-uniform flow field due to wingtip vortex would cause the flap to reach an equilibrium β that is smaller than the optimal β, thus reducing the additional lift generated.…”
mentioning
confidence: 88%